2022
DOI: 10.3390/ani12121591
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Fucoidan Supplementation on Serum Biochemical Parameters, Small Intestinal Barrier Function, and Cecal Microbiota of Weaned Goat Kids

Abstract: The purpose of this study was to evaluate the effects of fucoidan supplementation on serum biochemical parameters, small intestinal barrier function, and cecal microbiota of weaned goat kids. A total of 60 2-month-old weaned castrated male goat kids (Chuanzhong black goat) were used in this 30-day experiment. The goat kids were randomly divided into four groups: a control group (CON) fed the basal diet, and three other groups supplemented with 0.1%, 0.3%, and 0.5% fucoidan in the basal diet (denoted as F1, F2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…While, Ruminococcus which is an enterotype, has been reported to be negatively correlated with arterial stiffness and inflammatory adipokine levels [75] . Also, Yang et al [76] reported changes made to the phylum upon supplementation with fucoidan. Lastly, Desulfovibrio is one of the major sulfate-reducing bacteria in the human gut microbiome and the major metabolite (hydrogen sulfite) produced by this bacterium has been shown to have antiinflammatory, anti-proliferative effects and its potential in inhibiting restenosis [77][78] .…”
Section: Discussionmentioning
confidence: 99%
“…While, Ruminococcus which is an enterotype, has been reported to be negatively correlated with arterial stiffness and inflammatory adipokine levels [75] . Also, Yang et al [76] reported changes made to the phylum upon supplementation with fucoidan. Lastly, Desulfovibrio is one of the major sulfate-reducing bacteria in the human gut microbiome and the major metabolite (hydrogen sulfite) produced by this bacterium has been shown to have antiinflammatory, anti-proliferative effects and its potential in inhibiting restenosis [77][78] .…”
Section: Discussionmentioning
confidence: 99%
“…However, we have failed to identify the specific reasons and mechanisms of IL-6 in this study was lower than those in the control group, which needs further study. AST and ALT have the function of catalyzing the conversion of amino acids into keto acids and are considered to be crucial transaminase enzymes in various biological processes ( Yang et al, 2022 ). Under normal circumstances, the activity of ALT and AST in the body’s serum is low.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, EAR-H significantly increased serum GAS levels in SDD rats, indicating that this medication improved gastrointestinal function. DAO is a marker of intestinal barrier dysfunction [ 21 ] that is released into the blood when the intestinal barrier function becomes impaired. D-lactate, which is primarily formed by bacterial fermentation (e.g., Lachnospiraceae_NK4A136_group) in the intestine [ 22 ], correlates with an increase in intestinal permeability.…”
Section: Discussionmentioning
confidence: 99%